Lack of Intensity Control during an Exercise Program Is Related to a Limited Effect on Variables Responsible for Blood Pressure Regulation in Hypertensive Older Adults - Da Silva, Roberta Fernanda [UNESP]; Reia, Thaís Amanda [UNESP]; Jacomini, André Mourão [UNESP]; Da Silva, Anderson Bernadino [UNESP]; Dos Santos Disessa, Henrique [UNESP]; Monteiro, Henrique Luiz [UNESP]; Zago, Anderson Saranz [UNESP] (Wiley, 2024)
To compare the effect of an intensity-controlled exercise program (ICEP) and a nonintensity-controlled exercise program (non-ICEP) on the variables responsible for blood pressure regulation in hypertensive older adults. 95 hypertensive older adults (65.40 ± 7.48 years/22 males and 73 females) performed hemodynamic, functional fitness, and biochemical evaluations before and after 12 weeks of the multicomponent exercises which included walking, muscle strength, hydrogymnastics, Pilates, dynamic balance, agility, flexibility, and others. A significant improvement was observed in general functional fitness index (GFFI: p≤0.000, d = 0.35), nitrite (NO2-: p≤0.000, d = 0.49), systolic blood pressure (SBP: p≤0.000, d = 0.65), diastolic blood pressure (DBP: p≤0.013, d = 0.40), thiobarbituric acid reactive substances (TBARS: p≤0.007, d = 0.78), activity of the endothelial superoxide dismutase enzyme (ecSOD: p≤0.032, d = 0.41), double product (DP: p≤0.015, d = 0.43), and waist-hip ratio (WHR: p≤0.000, d = 0.44) for ICEP. Only GFFI (p≤0.047, d = 0.12), TBARS (p≤0.000, d = 0.77), SOD (p≤0.025, d = 0.25), DP (p≤0.046, d = 0.26), and BMI (p≤0.018, d = 0.02) presented better results in non-ICEP. When the effect of the groups (controlled by age, BMI, and sex) was evaluated, an increase was observed in the NO2-, TBARS, and SOD and a reduction in the SBP and WHR variables in the ICEP group compared to the non-ICEP group. Twelve weeks of engagement in a controlled-intensity exercise program was enough to improve the level of functional fitness and variables regarding blood pressure regulation in hypertensive older adults. Conversely, physical exercise performed without intensity control was related to the limited effect on such variables.